Al Jam’iyatul Washliyah dan Problem Kepemimpinan Non Muslim dan Perempuan - Jafar Jafar (AHKAM : Jurnal Ilmu Syariah, 2017)
Al-Washliyah as an organization engaged in education, da'wah,social charity and Islamic law, faces challenges in responding to current issues of non-Muslim and female leadership. This article examines Al-Washliyah'slegal view of non-Muslim leaders and women. This study found Al-Wasliyah's dissent of non-Muslim leadership and women. Organisationally, Al-Washliyah's Fatwa Council rejects non-Muslims as leaders for Muslim societies, although there are some scholars and intellectuals of Al-Washliyah who have different opinion on non-Muslim leaders. Also, this organization does not allow women to become heads of state, although some of Al-Washliyah's young intellectuals do not mind if women become heads of state. DOI: 10.15408/ajis.v17i2.5204